Detection of Shiga toxin producing Escherichia coli in endocervix of asymptomatic pregnant women: Novel pathogen responsible for adverse pregnancy outcomes? - Scalise, Maria Lujan (2021)
Brief Introduction: Some studies have demonstrated that vaginal E. coli colonization may produce complicationsduring pregnancy. We have previously reported that Shiga toxin-2 (Stx2) secreted by enterohemorrhagic E. coli canproduce abortion and premature delivery in animals and can impair human trophoblast in vitro.Objective: The aim of this study was to detect virulence factor genes from Shiga toxin producing E. coli (STEC)in the endocervix of asymptomatic pregnant women. Methods: Endocervical swabs were collected from 103 pregnantwomen (12 to 30 weeks of pregnancy) during their antenatal examination. Swab samples were enriched in TrypticSoy Broth overnight at 37 °C and then streaked into selective and differential medium, Sorbitol MacConkey agar. E.coli detection was confirmed by identification of uidA gene by PCR assay. Then, positive samples for E. coli wereanalyzed for STEC virulence factors genes: stx1, stx2, eae, rfbO157, lpfAO113 and hcpA. After that, positive E. colisamples for stx2 gene were grown in Luria-Bertani Broth medium in order to evaluate Stx2 cytotoxic activity. Forthat, the bacterial supernatants were filter-sterilized and cytotoxicity was evaluated on Vero, Swan 71 and HeLa cells.Results: Our results showed that 14.5% of the endocervical samples were positive for E. coli (positive for uidAgene). Furthermore, 9/15 (60%) of the E. coli-positive samples carried the stx2 gene and 6/15 (40%) carried thelpfAO113 and hcpA genes. One bacterial supernatant from an E. coli-positive endocervical sample carrying stx2 andlpfAO113 genes exhibited high cytotoxic activity on the cells evaluated due to Stx2 production confirmed by specificneutralization of Stx2 with an anti-Stx2 antibody.Conclusions: The novelty of this report is the presence of STEC in the endocervix of asymptomatic pregnantwomen. This opens a new perspective with respect to the possible role of this pathogen in woman reproductivehealth care.